Halalpreneur Opportunities and Challenges: Empirical Evidence from Indonesia - Sadali, Ayatullah; Fikri, Muhammad Khoirul; Adinugraha, Hendri Hermawan (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2024)
Purpose: This research aims to explain the business opportunities and challenges of the halal industry in Indonesia for HalalpreneursDesign/methodology: This qualitative research has used a literature review approach and adopts a content analysis methodologyFindings: The findings of this literature review show that the primary goal of a Halalpreneur is to achieve happiness in ad-daraini. Synonyms for the term Halalpreneur are Islamicpreneur, Shariapreneur, and Muslimpreneur. The substantive meaning of these terms is the same. Everything has the same essence as Halalpreneur. The opportunity and potential of the Indonesian state compared to other countries in developing the Islamic economy are strengthening the halal industry sectorPractical implications: The empirical implication of this research is to describe the halal industrial business still has the opportunity to become an alternative to Halalpreneur, such as Islamic tour travel, Islamic fashion, halal cosmetics, halal culinary, halal spa, and Sharia online motorcycle taxi services. The challenge facing the Indonesian nation today is the need for Halalpreneurs. The challenge ahead for the Indonesian people is the need to play a more active role in the halal industry. Another challenge is their need for more participation in advancing entrepreneurial activities at the micro and macro levels. These implications provide a clear roadmap for potential Halalpreneurs in Indonesia. Originality/Value: Halalpreneurs are very important for economic growth in Indonesia, according to Sharia, and they benefit all humanityKeywors: Halalpreneur; Entrepreneurship; Opportunities; Challenges